2018
DOI: 10.12944/crnfsj.6.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Improvement in Malnourished Rat (Rattus norvegicus) after Seluang Fish (Rasbora spp.) Treatment

Abstract: Prevalence of malnutrition in Indonesia is still high although it has some potential source of nutrients. Seluang fish (Rasbora spp.) is a river fish consumed by the people of South Kalimantan, Indonesia. This study analyzed the improvement of nutritional status in the malnourished rats after treatment with Seluang Fish. The study used malnourished white rats (Rattus norvegicus) using a low protein and fat diet for 8 weeks. The rats were divided into three groups; malnourished group (M) without other dietary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There is a fairly high protein, fat, amino acids content in kedawung seed tempeh flour (Parkia roxburghii G. Don) so that it helps increase the body weight of rats, after experiencing weight loss in PEM conditions. Protein plays an important role in the growth and maintenance of body tissues, as well as a source of energy for humans and animals, so it is possible to improve the nutritional status of rats with increased body weight (Triawanti, Yunanto, Sanyoto, & Nur'Amin, 2018). Essential amino acids play a major role in protein synthesis in the body related to the growth and development of children (Semba et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There is a fairly high protein, fat, amino acids content in kedawung seed tempeh flour (Parkia roxburghii G. Don) so that it helps increase the body weight of rats, after experiencing weight loss in PEM conditions. Protein plays an important role in the growth and maintenance of body tissues, as well as a source of energy for humans and animals, so it is possible to improve the nutritional status of rats with increased body weight (Triawanti, Yunanto, Sanyoto, & Nur'Amin, 2018). Essential amino acids play a major role in protein synthesis in the body related to the growth and development of children (Semba et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Protein malnutrition in animals can be induced by variations of composition and duration (weeks to months) of the feeding of restricted diets. The severity of malnutrition depends on the protein contents, namely, diets with low‐protein contents may induce severe malnutrition, whereas those with moderate protein contents may induce moderate malnutrition (Lobe, Marica, Bernstein, & C.,, & German, R.Z., ; Miñana‐Solis et al, ; Leite et al, ; Brito et al, ; Triawanti et al, ). In our experiments, the control rats received a normal quantity of protein, whereas the malnutrition model rats were prepared by providing them with low quantity of protein.…”
Section: Methodsmentioning
confidence: 99%
“…Composition of AIN-76A were casein 60 g/kg, DL-methionine 0.9 g/kg, sucrose 609.1 g/kg, cornstarch 183 g/kg, corn oil 50 g/kg, cellulose 50 g/kg, mineral mix#200000 35 g/kg, vitamin mix #300050 10 g/kg, choline bitartrate 2 g/kg. Rats are considered undernourished when plasma protein levels <4,7 g/dL [6]. R. norvegicus's normal protein level is 4,7e5,2 g/dL [7].…”
Section: Preparation Of Experimental Animals Malnutritionmentioning
confidence: 99%
“…South Kalimantan has a variety of potential food sources to overcome the problem of undernourished. Previous studies have shown that giving of wild fish from South Kalimantan can increase IGF-1, bone growth, Hb levels, protein [6], overcome oxidative stress in the brain [7], and improve memory [8] in mice that were malnourished.…”
Section: Introductionmentioning
confidence: 99%